Post Mastectomy Quality of Life in Breast Cancer Patients (Journal of Surgical Sciences, 2019)
Background: Quality of life in patients with breast cancer is an important outcome. This paper presents an overview and outcome after surgery in breast cancer patients on the topic ranging from descriptive findings to clinical trials.Methods: This is a bibliographic review of the literature covering publications that appeared in English language in biomedical journals between 1992 and 2013. The search strategy included a combination of key words 'quality of life' and 'breast cancer', 'breast carcinoma' or post mastectomy in Titles. Of these, research articles like randomized controlled trials, reviews, abstracts, editorials, brief commentaries, letters were included. The major findings are summarized and presented under several headings: instruments used, validation studies, measurement issues, surgical treatment, quality of life as predictor of survival, psychological distress, supportive care, symptoms and sexual functioning.Results: Instruments-Several valid instruments were used to measure quality of life in breast cancer patients. The European Organization for Research and Treatment of Cancer Core Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and its breast cancer specific complementary measure (EORTC QLQ-BR23) were listed in this study, as it is a common, highly standard and well developed instruments to measure quality of life in breast cancer patients. Different surgical procedures led to relatively similar results in terms of quality of life assessments, although mastectomy patients compared to conserving surgery patients usually reported a lower body image and sexual functioning. Systemic therapies-almost all studies indicated that breast cancer patients receiving chemotherapy might experience several side-effects and symptoms that negatively affect their quality of life. Adjuvant hormonal therapies also were found to have similar negative impact on quality of life, although in general they were associated with improved survival. Quality of life as predictor of survival-similar to known medical factors, quality of life data in metastatic breast cancer patients were found to be prognostic and predictive of survival time. Psychological distress-anxiety and depression were found to be common among breast cancer patients even years after the disease diagnosis and treatment. Psychological factors also were found to predict subsequent quality of life or even overall survival in breast cancer patients. As recommended, recognition and management of these symptoms is an important issue since such symptoms impair health-related quality of life. Sexual functioning-breast cancer patients especially younger patients suffer from poor sexual functioning that negatively affect quality of life.Conclusion: There was quite an extensive body of the literature on quality of life in breast cancer patients. These papers have made a considerable contribution to improving breast cancer care, although their exact benefit was hard to define. However, quality of life data provided scientific evidence for clinical decision-making and conveyed helpful information concerning breast cancer patients' experiences during the course of the disease diagnosis, treatment, disease-free survival time, and recurrences.Journal of Surgical Sciences (2013) Vol. 17 (1) : 35-44